Characterisation of flame-generated soot and soot-in-oil using electron tomography volume reconstructions and comparison with traditional 2D-TEM measurements - Orhan, O.; Haffner-Staton, Ephraim; La Rocca, Antonino; Fay, Mike W. (Elsevier, 2016)
This work characterises soot nanoparticles by electron tomography using Weighted Back Projection algorithm and appraises the uncertainties in two-dimensional calculations by comparison with 3D parameters for flame-generated soot and diesel soot-in-oil. Bright field TEM was used to capture 2D images of soot. Large uncertainties exist in 2D-measured morphological parameters. The flame-generated particle showed an extensive 3D structure while the soot-in-oil was notably two-dimensional. Morphological parameters of flame-generated soot and diesel soot-in-oil were different; primary particles, volume, and surface area varied significantly over the range of viewing angle, with differences as large as 60%. 2D flame-generated soot volume underestimated 3D measurements by 38%; soot-in-oil 2D and 3D-derived volumes were within 4%. 2D calculations of fractal dimension generally underestimate the 3D value.